Variation in Tularemia Clinical Manifestations—Arkansas, 2009–2013. (15th February 2017) - Lester Rothfeldt, Laura K.; Jacobs, Richard F.; Wheeler, J. Gary; Weinstein, Susan; Haselow, Dirk T.
Abstract: Background: Francisella tularensis, although naturally occurring in Arkansas, is also a Tier 1 select agent and potential bioterrorism threat. As such, tularemia is nationally notifiable and mandatorily reported to the Arkansas Department of Health. We examined demographic and clinical characteristics among reported cases and outcomes to improve understanding of the epidemiology of tularemia in Arkansas. Methods: Surveillance records on all tularemia cases investigated during 2009–2013 were reviewed. Results: The analytic dataset was assembled from 284 tularemia reports, yielding 138 probable and confirmed tularemia cases during 2009–2013. Arthropod bite was identified in 77% of cases. Of 7 recognized tularemia manifestations, the typhoidal form was reported in 47% of cases, approximately double the proportion of the more classic manifestation, lymphadenopathy. Overall, 41% of patients were hospitalized; 3% died. The typhoidal form appeared to be more severe, accounting for the majority of sepsis and meningitis cases, hospitalizations, and deaths. Among patients with available antibiotic data, 88% received doxycycline and 12% received gentamicin. Conclusions: Contrary to expectation, lymphadenopathy was not the most common manifestation observed in our registry. Instead, our patients were more likely to report only generalized typhoidal symptoms. Using lymphadenopathy as a primary symptom to initiate tularemia testing may be an insensitive diagnostic strategy and result in unrecognized cases. In endemic areas such as Arkansas, suspicion of tularemia should be high, especially during tick season. Outreach to clinicians describing the full range of presenting symptoms may help address misperceptions about tularemia.